C. Cremonini's Treatises in Lithuania - Plečkaitis, Romanas (Problemos, 1969)
In the manuscript department of the Scientific Library of the Vilnius V. Kapsukas State University (signature F3-2015; F3-2057) are kept lecture notes on physics and psychology of Cesare Cremonini, a famous Italian philosopher of the Renaissance. They render the principal ideas of C. Cremonini, condemned by the Inquisition. The course of lectures in question was read by C. Cremonini in the University of Padua at the beginning of the 17th century. The notes, it is assumed, were brought to Lithuania by the offsprings of the Lithuanian nobility who studied in Italian higher schools.